2020
DOI: 10.1007/s10964-020-01306-x
|View full text |Cite
|
Sign up to set email alerts
|

Effortful Control and Community Violence Exposure as Predictors of Developmental Trajectories of Self-serving Cognitive Distortions in Adolescence: A Growth Mixture Modeling Approach

Abstract: Self-serving cognitive distortions are biased or rationalizing beliefs and thoughts that originate from the individual persistence into immature moral judgment stages during adolescence and adulthood, increasing the individual’s engagement in antisocial or immoral conducts. To date, the literature examining trajectories of cognitive distortions over time and their precursors is limited. This study sought to fill this gap, by examining effortful control and community violence exposure as individual and environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 59 publications
(81 reference statements)
2
11
0
Order By: Relevance
“…In a qualitative study, Wilkinson and Carr (2008) outlined that individuals respond to exposure to violence in many ways, some of which are consistent with traditional concepts of moral disengagement or emotional numbing. Similarly, Esposito et al (2020) found that among adolescents, exposure to community violence predicts high and persistent levels of cognitive distortions over a 4 year time period.…”
Section: Introductionmentioning
confidence: 89%
“…In a qualitative study, Wilkinson and Carr (2008) outlined that individuals respond to exposure to violence in many ways, some of which are consistent with traditional concepts of moral disengagement or emotional numbing. Similarly, Esposito et al (2020) found that among adolescents, exposure to community violence predicts high and persistent levels of cognitive distortions over a 4 year time period.…”
Section: Introductionmentioning
confidence: 89%
“…However, there is a great amount of evidence highlighting the negative effects of community violence exposure on moral development. The research found that children and adolescents exposed to community violence, fail in distinguishing moral vs. conventional issues ( Bacchini et al, 2013 ), tend to make frequent recourse to self-serving cognitive distortions ( Dragone et al, 2020 ; Esposito et al, 2020 ), judge morally acceptable physically harming others in contexts of survival or revenge ( Posada and Wainryb, 2008 ), and are more likely to condone moral transgressions when provoked or for reasons of retaliation ( Ardila-Rey et al, 2009 ). Overall, exposure to violence has been found to substantially disrupt the moral decision-making ability as a result of impairments of several emotional (e.g., empathy), cognitive (e.g., theory of mind), and inhibitory control abilities ( Zucchelli and Ugazio, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Social Cognitive Theory (SCT) posits that a cognitive process occurs when an individual experiences events within their environment (Bond & Bushman, 2017; Esposito et al, 2020), this includes interpretations, attributions, and inferences, that then become internalized and lead to generalizations in behaviors (Bandura, 1986; Esposito et al, 2020). This serves the function of determining appropriate behavioral responses in a particular environment and developing competency in how to respond over time (Bandura, 1986; Esposito et al, 2020). Thus, individuals develop what they believe is a normative response to provide a purposeful action (Esposito et al, 2020).…”
Section: Social Cognitive Theory In the Context Of Violencementioning
confidence: 99%
“…behaviors (Bandura, 1986;Esposito et al, 2020). This serves the function of determining appropriate behavioral responses in a particular environment and developing competency in how to respond over time (Bandura, 1986;Esposito et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation